Acute Encephalitis with Atypical Presentation of Rubella in Family Cluster, India - Bharadwaj, Sumit D. (Emerg Infect Dis, 2018)
We report 3 atypical rubella cases in a family cluster in India. The index case-patient showed only mild febrile illness, whereas the other 2 patients showed acute encephalitis and died of the disease. We confirmed rubella in the index and third cases using next-generation sequencing and IgM.